A Literature Study to Characterize Continuous Experimentation in Software Engineering - Erthal, Vladimir M.; de Souza, Bruno P. de; Santos, Paulo Sérgio M. dos; Travassos, Guilherme H. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
Continuous Experimentation (CE) has become increasingly popular across industry and academic communities. Given its rapid evolution in software engineering (SE), the lack of a common understanding of CE can jeopardize new implementations and justify research efforts. Therefore, this literature study characterizes CE in SE based on its definitions, processes, and strategies for experimentation available in the technical literature. Seventy-six sources of information provided many different definitions, processes, and experimental procedures used to describe CE in SE. Despite the increasing use of CE in SE, it is impossible to observe a common terminology yet to support its characterization and use.